Intelligent Point-of-Care Biosensing Platform Based on Luminescent Nanoparticles and Microfluidic Biochip with Machine Vision Algorithm Analysis - Liu, Yuan; Lao, Xinyue; Wong, Man‑Chung; Song, Menglin; Zhao, Yifei; Ma, Yingjin; Bai, Qianqian; Hao, Jianhua (Nano-Micro Letters, 2025)
Realizing the point-of-care tumor markers biodetection with good convenience and high sensitivity possesses great significance for prompting cancer monitoring and screening in biomedical study field. Herein, the quantum dots luminescence and microfluidic biochip with machine vision algorithm-based intelligent biosensing platform have been designed and manufactured for point-of-care tumor markers diagnostics. The employed quantum dots with excellent photoluminescent performance are modified with specific antibody as the optical labeling agents for the designed sandwich structure immunoassay. The corresponding biosensing investigations of the designed biodetection platform illustrate several advantages involving high sensitivity (~ 0.021 ng mL−1), outstanding accessibility, and great integrability. Moreover, related test results of human-sourced artificial saliva samples demonstrate better detection capabilities compared with commercially utilized rapid test strips. Combining these infusive abilities, our elaborate biosensing platform is expected to exhibit potential applications for the future point-of-care tumor markers diagnostic area. Highlights: 1 A novel intelligent biosensing platform consisting of quantum dots luminescence and biochip with machine vision algorithm is proposed for point-of-care carcinoembryonic antigen (CEA) protein diagnostics. 2 The designed diagnostic platform possesses outstanding detection limitation of approximately 0.021 ng mL−1 of CEA concentration compared with some commercial biodetection devices of lateral flow assay strips. 3 The utilization of machine vision algorithm improves the detection features of portability and integration, which expands the potential of point-of-care biosensing applications.